2015
DOI: 10.1177/0956797615577619
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Trumps Vision in Training Attention

Abstract: Mental imagery can have powerful training effects on behavior, but how this occurs is not well understood. Here we show that even a single instance of mental imagery can improve attentional selection of a target more effectively than actually practicing visual search. By recording subjects’ brain activity, we show that these imagery induced training effects were due to perceptual attention being more effectively focused on targets following imagined training. Next, we show the downside of this potent training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
31
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 27 publications
6
31
0
Order By: Relevance
“…An interesting recent study by Reinhart et al (2015) demonstrated that attentional mechanisms can be effectively trained to select target objects through visualization. Moreover, they found that visualizing search for a particular target in an imagined array can speed reaction time to find the target on a subsequent trial even more than actually searching for the target in an array presented on the screen.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…An interesting recent study by Reinhart et al (2015) demonstrated that attentional mechanisms can be effectively trained to select target objects through visualization. Moreover, they found that visualizing search for a particular target in an imagined array can speed reaction time to find the target on a subsequent trial even more than actually searching for the target in an array presented on the screen.…”
Section: Introductionmentioning
confidence: 99%
“…If it is the case that visualization is more effective because it isolates the facilitative components of the task, for example, vague or incomplete representations may in fact be superior to less vivid or detailed ones. We therefore plan to first replicate the original study by Reinhart et al (2015), focusing specifically on the behavioral results. Omitting the recording of EEG allows us to use a slightly simplified stimuli design to test the original results, without the second irrelevant colored distractor (only included in the original study to allow for comparison of the lateralized N2PC component between the two Hemifields).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations